"Somewhere, over the rainbow": Representations of the European Union in light of the ongoing European integration of the Republic of Serbia - Marija Brujić (University of Belgrade, 2016)
About a book of Bojan Žikić, "Slike u izlogu. Kulturne predstave o Evropskoj uniji kao sredstvo opisivanja paralelne stvarnosti stanju u Srbiji 1991-2011", Beograd, 2013. ("Shop Windows Reflections: Cultural Notions of EU as a Tool for Representing the Reality Comprehended as Parallel to the One of Serbia 1991-2011")